Responsivitas Pelayanan Pengaduan Masyarakat Di Kepolisian Sektor Kecamatan Uluere Kabupaten Bantaeng - Kurniasih, Dwi Ratna; Parawangi, Anwar; Andriana, Andriana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed  to describe and explain the responsiveness of public complaints services in the Sector Police of Uluere District, Bantaeng Regency. This study used qualitative descriptive research type. There were 11 informants in this study. Data collection techniques used observation, interviews and documentation. The results showed that the responsiveness of public complaints services at the Uluere District Police was good. Uluere District Sector Police officers were friendly and polite when providing services to the community. The apparatus had served quickly, they swiftly served the people who came to report. They  had done the service carefully, they  provided services seriously and earnestly so that no mistakes occur. They also had served on time, although it was not optimal, all processes were carried out immediately without stalling, but the apparatus was still not disciplined because there were still people waiting because they had not arrived  office on time. Keywords: Responsiveness, Service, Public Complaints